Serum aminotransferase ratio is independently correlated with hepatosteatosis in patients with HCV: a cross-sectional observational study. Issue 9 (14th September 2015) - Lin, Ming-Shyan; Lin, Huang-Shen; Chung, Chang-Ming; Lin, Yu-Sheng; Chen, Mei-Yen; Chen, Po-Han; Hu, Jing-Hong; Chou, Wen-Nan; Huang, Jui-Chu; Huang, Tung-Jung
Abstract : Objectives: The incidence of non-alcoholic fatty liver disease (NAFLD) is significant in hepatitis C virus (HCV) carriers due to multiple mechanisms, and this worsens the progression of chronic liver diseases, such as cirrhosis and hepatocellular carcinoma, and death. The purpose of this study was to examine whether the alanine aminotransferase/aspartate aminotransferase (ALT/AST) ratio correlates with the status of hepatosteatosis. Design: A cross-sectional observational study. Setting: Community-based annual examination in northern Taiwan. Participants: A total of 1354 participants (age 20 years or over) were enrolled after excluding participants with HCV seronegative, laboratory or questionnaires loss, moderate alcohol consumption, liver cirrhosis, tumours and postlobectomy. Outcome measures: Fatty liver was diagnosed according to echogenic findings. NAFLD included grades 1–3 fatty liver and high-degree NAFLD defined grades 2–3 fatty liver. Results: 580 males and 774 females with a mean age of 47.2 (SD=16.1) years were cross-sectionally studied. The participants with NAFLD have significantly higher levels of ALT/AST ratio, fasting glucose, triglyceride and systolic/diastolic blood pressure than non-NAFLD participants. The association between NAFLD and ALT/AST was significant even when adjusting for the metabolic syndrome (aOR 1.90; 95% CI 1.37 to 2.65; p<0.001). In patients with a high degree of NAFLD, the ALT/AST ratio was still a significant predictor for hepatosteatosis (aOR 2.44; 95% CI 1.58 to 3.77; p<0.001). Conclusions: The ALT/AST ratio could be a strong risk of hepatosteatosis in patients with chronic HCV infection.